Immunosuppression in sepsis and possibility of its correction - M. V. Kiselevskii; S. M. Sitdikova; A. G. Abdullaev; S. A. Shlyapnikov; I. O. Chikileva (Вестник хирургии имени И.И. Грекова)
Literature review is devoted to immunosuppression in sepsis and possibilities of its correction.